BRIDGING FAITH AND PRAXIS: Everyday Theology and the Cultural Mandate in Post-Suramadu Madura - Ana Budi Kristiani; Njoo Tomas Wibowo; Vian Klasia Wenno; Isak Suria; Beanto Benny (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This study examines the role of everyday theology in relation to the cultural mandate and its practical implementation in post-Suramadu Madura. Employing a descriptive qualitative approach, data were collected through questionnaires distributed to five churches. The findings indicate that while theological understanding of culture (100%), creation (80%), and economy (80%) is relatively strong, its practical implementation across key sectors remains limited, including agriculture (20%), livestock (0%), tourism (20%), education (20%), and healthcare (40%). These results reveal a significant gap between theological understanding and ecclesial praxis. This study argues that everyday theology can function as a praxis-oriented framework that enables churches to engage more contextually and holistically with socio-economic realities. It contributes to practical theology by demonstrating how everyday theology bridges the gap between theological reflection and lived practice in the post-Suramadu Madurese context.